Islam's Contribution to Upholding Human Rights (HAM) and Preventing Racism - Alisah Ayu Ningrum; Didik Himmawan; Mulia Uchti Cholifah (Aslama: Journal of Islamic Studies, 2025)
Islam has made significant contributions to the enforcement of Human Rights (HAM) and the prevention of racism, as reflected in the fundamental teachings of the Qur'an and Hadith. This study aims to analyze how Islamic principles support respect for human rights, as well as the role of religion in reducing racial discrimination. Islam teaches equality before God, emphasizing that all humans come from the same origin, namely Adam and Eve. This teaching encourages respect for the dignity of individuals regardless of ethnicity, race, or social status. Using a qualitative approach, this study examines various texts and interpretations that underlie the concept of human rights in Islam and its implementation in social life. The results show that although challenges in its implementation still exist, Islam has provided a strong foundation in advocating for basic human rights and overcoming racist practices in society. In conclusion, Islamic principles can be used as an important reference in global efforts to promote human rights and reduce racial discrimination.